Addictions Neuroclinical Assessment: A reverse translational approach. (1st August 2017) - Kwako, Laura E.; Momenan, Reza; Grodin, Erica N.; Litten, Raye Z.; Koob, George F.; Goldman, David
Abstract: Incentive salience, negative emotionality, and executive function are functional domains that are etiologic in the initiation and progression of addictive disorders, having been implicated in humans with addictive disorders and in animal models of addictions. Measures of these three neuroscience-based functional domains can capture much of the effects of inheritance and early exposures that lead to trait vulnerability shared across different addictive disorders. For specific addictive disorders, these measures can be supplemented by agent specific measures such as those that access pharmacodynamic and pharmacokinetic variation attributable to agent-specific gatekeeper molecules including receptors and drug-metabolizing enzymes. Herein, we focus on the translation and reverse translation of knowledge derived from animal models of addiction to the human condition via measures of neurobiological processes that are orthologous in animals and humans, and that are shared in addictions to different agents. Based on preclinical data and human studies, measures of these domains in a general framework of an Addictions Neuroclinical Assessment (ANA) can transform the assessment and nosology of addictive disorders, and can be informative for staging disease progression. We consider next steps and challenges for implementation of ANA in clinical care and research. This article is part of the Special Issue entitled "Alcoholism". Highlights: This review describes three neuroscience domains relevant for addiction. These comprise Incentive Salience, Negative Emotionality and Executive Function. Preclinical and clinical addiction studies show alterations in these domains. The domains can assist translational and reverse translational addictions research.